RÂŞİD EL-GANNÛŞÎ VE SİYASET ANLAYIŞI - ÖZTÜRK, AYSEL (Fırat Üniveristesi, 2018)
Râşid el-Gannûşî, hem bir düşünür hem de İslâmî hareket lideri olarak son yıllarda çağdaş İslâm düşüncesine yön veren ve küresel İslâmî çevrelerce itibar edilen bir otoritedir. Onu diğer İslâm siyaseti düşünürlerinden ayıran şey ise, siyasete doğrudan dahil olmasıdır. Zira kendisi Tunus siyasetinde önemli bir yere sahip olan Nahda Hareketi lideridir. Râşid el-Gannûşî; demokrasi ve İslâm arasındaki ilişkiyi yeniden düşünmesi, İslâmî özgürlük ve insan hakları kavramlarını izah etmesi, sivil toplum dilini yeniden tanımlaması, laiklik ve sivil toplum kavramlarının bağdaşmadığı şeklindeki düşünceleri ile İslâm dünyasında ve Batı'da yansımaları olan bir düşünürdür. Merkeze İslâm'ı alarak bu kavramlara yaklaşan Gannûşî'nin fikirleri İslâm dünyası için önemlidir. Bu bakımdan çalışmamızın ana mevzusunu Gannûşî'nin siyaset anlayışı oluşturmaktadır. Ayrıca Gannûşî'nin hayatı, zihin dünyasının şekillenmesinde etken olan âmiller ve kurmuş olduğu Nahda Hareketi, çalışmamızda değindiğimiz diğer konuları oluşturmaktadır.

Rachid al-Ghannouchi, both a thinker and leader of the Islamic movement, is an author that has given way to contemporary Islamic thought in the recent years and is reputed in the global Islamic circles. What distinguishes him from other thinkers of Islamic politics is that politics is directly involved. Because he is the leader of the Nahda Movement which has an important place in Tunisian politics Rachid al-Ghannouchi is a thinker who has reflections with rethinking relationship between democracy and Islam, explaining concepts of Islamic freedom and human rights, redefining the language of the civil society, the thoughts of incongruity between the concepts of secularism and civil society in the Islamic world and in the West. The ideas of Gahnnouchi who approaches these concepts by taking Islam at the center, are important for the Islamic world. In this respect, the main point of our work constitutes Gahhanouchi's political thoughts. Moreover, Ghannouchi's life, the factors shaping his mind world and Nahda Movement which he founded, constitutes other subjects that we have mentioned in our work.
Rachid al-Ghannouchi and understanding of politics
Keywords: Din